Suppression of subsynchronous vibrations due to aerodynamic response to surge in a two-stage centrifugal compressor with air foil bearings - Lee, YB; Kim, TH; Kim, CH; Lee, NS (SOC TRIBOLOGISTS & LUBRICATION ENGINEERS, 2003)
An investigation was conducted on the suppression of subsynchronous vibrations due to aerodynamic response to surge in a two-stage centrifugal compressor with air foil bearings. Unsteady aerodynamic response to surge caused excessive subsynchronous shaft vibration which might result in reduced bearing life. Notably, subsynchronous vibrations associated with rigid mode frequencies were more severe than any other subsynchronous vibrations. The objective was to develop rotordynamic stability near the surge line in a two-stage compressor by the modification of bearings into high damping foil bearings. Viscoelastic foil bearings, which consist of a viscoelastic top foil supported by a series of bump foils, were adapted to replace bump type foil bearings in a two-stage compressor. Investigations were made in the form of a compressor operating test near the surge line with the conventional bump foil bearing and the viscoelastic foil bearing respectively. Test results showed the effectiveness of the viscoelastic foil bearing for suppressing the subsynchronous vibrations, including subsynchronous vibrations associated with rigid mode frequencies of the shaft. Thus, rotordynamic stability was improved with a viscoelastic foil bearing, which has enhanced damping characteristics near the surge line.
Keywords: JOURNAL BEARINGS